Annual Ambient Black Carbon Associated with Shorter Telomeres in Elderly Men: Veterans Affairs Normative Aging Study - McCracken, John; Baccarelli, Andrea; Hoxha, Mirjam; Dioni, Laura; Melly, Steve; Coull, Brent; Suh, Helen; Vokonas, Pantel; Schwartz, Joel (Environmental health perspectives, 2010)
Background: Telomere length reflects biological age and is inversely associated with risk of cardiovascular disease (CVD). Ambient air pollution is associated with CVD, but its effect on telomere length is unknown. Objective: We investigated whether ambient black carbon (BC), a marker for traffic-related particles, is associated with telomere length in the Normative Aging Study (NAS). Methods: Among 165 never-smoking men from the NAS, leukocyte telomere length (LTL) was measured repeatedly approximately every 3 years from 1999 through 2006 using quantitative realtime polymerase chain reaction (qRT-PCR). BC concentration at their residences during the year before each LTL measurement was estimated based on a spatiotemporal model calibrated with BC measurements from 82 locations within the study area. Results: The median [interquartile range (IQR)] annual moving-average BC concentration was 0.32 (0.20-0.45) µg/m³. LTL, expressed as population-standardized ratio of telomere repeat to single-copy gene copy numbers, had a geometric mean (geometric SO) of 1.25 (1.42). We used linear mixed-effects models including random subject intercepts and adjusted for several potential confounders. We used inverse probability of response weighting to adjust for potential selection bias due to loss to follow-up. An IQR increase in annual BC (0.25 µg/m³) was associated with a 7.6% decrease (95% confidence interval, -12.8 to -2.1) in LTL. We found evidence of effect modification, with a stronger association among subjects ≤ 75 years of age compared with younger participants (p = 0.050) and statin medications appearing protective of the effects of BC on LTL (p = 0.050). Conclusions: Telomere attrition, linked to biological aging, may be associated with long-term exposures to airborne particles, particularly those rich in BC, which are primarily related to automobile traffic.